Frontier Films (New York, N.Y.) records - Frontier Films (New York, N.Y.)
Financial records, personnel card files, scrapbook, photographs, and other records of Frontier Films. Scrapbook contains items relating to the feature-length film Native Land (1942).
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
A non-profit documentary filmmaking company comprised of filmmakers on the political left who were devoted to producing artistic films relating to social and political issues. Major figures in the organization included Leo Hurwitz, Ralph Steiner, and Paul Strand. Split from New York Film and Photo League in 1934 to become Nykino; name changed to Frontier Films in 1937. Disbanded in 1942.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Hurwitz, Leo T., -- 1909-1991.; Steiner, Ralph, -- 1899-1986.; Strand, Paul, -- 1890-1976.; Nykino (Organization : New York, N.Y.); Native land (Motion picture : 1942); Motion pictures -- Political aspects; Motion pictures -- Production and direction; Motion pictures -- Social aspects